Does EOR in unconventionals change the rock?. (15th February 2022) - Sondergeld, Carl; Curtis, Mark; Dang, Son; Mamoudou, Sidi; Rai, Chandra
Highlights: EOR Unconventionals Microstructure Abstract: Recent interest in EOR in unconventionals, typically comprised of organic and inorganics, begs the question: does the process change the rock in measurable ways? We ran a series of EOR huff-n-puff experiments to assess hydrocarbon recoveries. We varied soak times, injection pressures and number of cycles, measured what was produced, and looked at the microstructure before and after the EOR huff-n-puff process. We have documented significant changes in the pore structure, in particular, in the organic component, which leads to increased porosity and connectivity and non-monotonic cyclic recovery efficiencies.